2015
DOI: 10.1136/bmjopen-2015-008650
|View full text |Cite
|
Sign up to set email alerts
|

Primary care consultation rates among people with and without severe mental illness: a UK cohort study using the Clinical Practice Research Datalink

Abstract: ObjectivesLittle is known about service utilisation by patients with severe mental illness (SMI) in UK primary care. We examined their consultation rate patterns and whether they were impacted by the introduction of the Quality and Outcomes Framework (QOF), in 2004.DesignRetrospective cohort study using individual patient data collected from 2000 to 2012.Setting627 general practices contributing to the Clinical Practice Research Datalink, a large UK primary care database.ParticipantsSMI cases (346 551) matched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(73 citation statements)
references
References 30 publications
(36 reference statements)
4
69
0
Order By: Relevance
“…The volume comparators used in this instance compare drug prescribing between different practices and they are designed to weight individual practice or organisation populations for age and sex while taking into account the different needs of people who will be receiving that treatment. All three mental illness measures were attributed to LSOAs using spatial methodologies (Kontopantelis et al, 2015b). More information on the data and the attribution methodology are provided in the online Supplementary material.…”
Section: Data Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…The volume comparators used in this instance compare drug prescribing between different practices and they are designed to weight individual practice or organisation populations for age and sex while taking into account the different needs of people who will be receiving that treatment. All three mental illness measures were attributed to LSOAs using spatial methodologies (Kontopantelis et al, 2015b). More information on the data and the attribution methodology are provided in the online Supplementary material.…”
Section: Data Sourcesmentioning
confidence: 99%
“…Moreover, cuts to local government budget and the benefit reforms have hit the most deprived and poorest parts of the country hardest, leading to widening health inequalities (Taylor-Robinson and Gosling, 2011;Crawford and Phillips, 2012;Barr et al, 2016). Finally, it is suggested that recording of SMI in primary care exhibits a greater increase in the most deprived areas (Kontopantelis et al, 2015a). Our models also indicated an unexpected negative association for prevalence of depression and antidepressant prescription volume with social fragmentation and we explored this association across different residential settings to conclude that there may be several reasons for the unexpected association observed.…”
Section: Interpretation Of the Findingsmentioning
confidence: 99%
“…We found slightly lower levels of continuity than those in an earlier study of family physician continuity for people with long-term mental illness in the United Kingdom, 53 but much lower than those found in studies looking only at specialist mental health care. 17,18 Higher, and rising, 54 rates of consultation in family practice may contribute to these differences. Relational continuity in English family practices may be affected by reductions in full-time working and increasing practice size.…”
Section: Discussionmentioning
confidence: 99%
“…The 2003/04 year was excluded as per previous studies[6], as some practices were preparing for the introduction of the QOF in the year prior to its introduction.…”
Section: Methodsmentioning
confidence: 99%